2022
DOI: 10.1002/ange.202202733
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation of Hydrogen Peroxide and Formate by an Organic Polymer Dots Photocatalyst in Alkaline Conditions

Abstract: A photocatalyst comprising binary organic polymer dots (Pdots) was prepared. The Pdots were constructed from poly(9,9-dioctylfluorene-alt-benzothiadiazole), as an electron donor, and 1-[3-(methoxycarbonyl)propyl]-1-phenyl-[6.6]C 61 , as an electron acceptor. The photocatalyst produces H 2 O 2 in alkaline conditions (1 M KOH) with a production rate of up to 188 mmol h À 1 g À 1 . The external quantum efficiencies were 30 % (5 min) and 14 % (75 min) at 450 nm. Furthermore, photo-oxidation of methanol by Pdots, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Moreover, the combination of Pdots with catalase results in the protection of hydrogenase against damage up to 0.3% O 2 in the headspace (Figure S24b in the SI). 81,82 In this case, Pdots and MV 2+ probably reduce molecular oxygen into H 2 O 2 (Figure S24a), 83 while the catalase efficiently dismutates produced H 2 O 2 to half a molecule of O 2 and water as a side product (Section IV in the SI).…”
Section: Preparation Of Pdotsmentioning
confidence: 99%
“…Moreover, the combination of Pdots with catalase results in the protection of hydrogenase against damage up to 0.3% O 2 in the headspace (Figure S24b in the SI). 81,82 In this case, Pdots and MV 2+ probably reduce molecular oxygen into H 2 O 2 (Figure S24a), 83 while the catalase efficiently dismutates produced H 2 O 2 to half a molecule of O 2 and water as a side product (Section IV in the SI).…”
Section: Preparation Of Pdotsmentioning
confidence: 99%
“… 34 36 Therefore, it is also likely that electron transfer to an active Pd site could also happen from an already protonated reduced polymer. 37 In this case, it is possible that the proton would transfer as well, as it has already been shown that BT sites will perform proton-coupled electron transfer reactions. 23 This certainly requires that the residual Pd be close enough to the active site.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the reductive quenching of PFBT by SDs to form reduced PFBT also seems to be an important pathway with 20–30% quenching in 30% DEA and 40% in ascorbic acid. , We can also see a clear reductive quenching of PFBT in organic media with ascorbic acid (Figures S14–S15) since this is a condition with sufficiently acidic protons that the reduced polymer is expected to rapidly be protonated. This is even more likely with ascorbic acid as it will also release a proton as it decomposes after being oxidized and therefore works like a proton-coupled electron transfer (PCET) donor and not just a simple reductive agent. Therefore, it is also likely that electron transfer to an active Pd site could also happen from an already protonated reduced polymer . In this case, it is possible that the proton would transfer as well, as it has already been shown that BT sites will perform proton-coupled electron transfer reactions .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Polymer dots (PDs) are typically cutting-edge nanosized polymeric materials (including conjugated PDs, carbonized PDs, etc.) that have attracted much attention because of their designable nanoarchitectural features, outstanding biocompatibility, tunable photoluminescent characteristics, and recyclability as nanophase . The common preparation methods for PDs, such as hydrothermal, nanoprecipitation, and miniemulsion, ordinarily lack in situ , real-time, and noncontact operability, and lack convenience from the perspective of material use.…”
Section: Introductionmentioning
confidence: 99%
“…PDs are typically formed by covalent or noncovalent bond linked nano-objects with polymer components up to a diameter of less than 10 nm. Therefore, for a light-induced synthesis method, particle-template-confined photopolymerization might be valid. Template-confined reactions, which can usually be promoted by molecular aggregation and solid states, have played a powerful role in the construction of various supramolecular or nanoarchitectures, , where the preorganization of the reactants is required for minimal atom displacement during the breaking and making of bonds.…”
Section: Introductionmentioning
confidence: 99%